Potential of Orbital Formed Tailored Blanks for Industrial Application - Hetzel, Andreas; Lechner, Michael; Aman, Alexander; Büdicker, Kai; Merklein, Marion (Steel in Cars and Trucks (SCT), 2022)
Due to economic and ecologic framework conditions like fuel reduction or sustainability, the manufacturing industry is facing greater challenges than ever before. One way to meet these challenges is the combination of lightweight construction and functional integration with an increased material efficiency. Nowadays, components like synchronizer rings or clutch plates are manufactured by machining, producing scrap and thus reducing the efficiency drastically. Orbital forming is an innovative manufacturing process, providing the possibility to efficiently produce functional components with a varying sheet thickness. Thereby, a tumbling motion of the punch reduces the contact area between workpiece and tool, thus enabling a significantly lower process force. The material distribution is realized by a tangential and radial material flow into the cavities. Until now, orbital formed Tailored Blanks have only been investigated as semi-finished products used in a single-stage process combination of deep drawing and upsetting. With regard on the potential for an industrial application, a Tailored Blank layout with different functional elements is introduced. The demonstrator for this investigation is manufactured out of the case-hardenable steel C10 and is depicting a clutch disc carrier with both-sided cyclic as well as rotational-symmetric material thickenings. To evaluate the industrial applicability, the components are analyzed regarding their geometrical and mechanical properties and are compared to the target contour. To demonstrate the operational advantages of the orbital formed components in comparison to conventionally manufactured parts, the fatigue life is evaluated as indicator for the functional behavior.<br
Keywords: Sheet-Bulk Metal Forming; Tailored Blank; Orbital Forming; Endurance Strength; Functional Component; Lightweight Design; Industrial Application